Combined Occurrence of Autosomal Dominant Aniridia and Autosomal Recessive Albinism in Several Members of a Family. (June 2015) - Yahalom, Claudia; Sharon, Dror; Dalia, Eli; Simhon, Shiran Ben; Shemesh, Efrat; Blumenfeld, Anat
Abstract Purpose: To characterize clinical and genetic aspects of a family with a unique combination of two hereditary blinding eye diseases. Methods: Comprehensive eye examination of proband and family members. Molecular analyses of the TYR and PAX6 genes. Results: A young couple, both legally blind, requested genetic counselling regarding their ocular condition. The female was previously diagnosed with oculocutaneous albinism (OCA1A) and her spouse was diagnosed with Peters anomaly. A comprehensive clinical examination revealed that the female had OCA1A combined with signs of another ocular disease, showing some similarity to aniridia. A complete ocular examination of her family members revealed that her brother also suffered from the same combined phenotype, her father had typical OCA1A signs, and her mother and sister had aniridia-like phenotype, without clinical diagnosis until the time of presentation. Molecular analysis identified two compound heterozygous TYR mutations known to cause OCAIA and cosegregate with oculocutaneous albinism. In addition, we identified a novel heterozygous PAX6 mutation confirming the atypical aniridia phenotype. Conclusions: We report here a unique and rare clinical phenotype that is explained by the segregation of two severe inherited eye diseases. The clinical and genetic analysis in this family allowed them to receive accurate genetic counseling.